L’ambivalence du conformisme langagier et communicationnel - Roger Bautier (Amnis)
If we analyze the norms that govern language and communication in society, and the consequences of these norms for political participation, we can see that linguistic and communicational conformism is ambivalent. A factor of social control by the selection it implies, it also constitutes an asset for those who manage to treat it as a weapon in a strategy aimed at an effective intervention within the public sphere. The development of new communication technologies has undoubtedly renewed the conditions for this participation, but to what extent ?